COMPARATIVE STUDY OF ION-EXCHANGE AND FLOTATION PROCESSES FOR THE REMOVAL OF Cu2+ AND Pb2+ IONS FROM NATURAL WATERS - Koyuncu, Ikbal; Akcin, Nurgul; Akcin, Goksel; Mutlu, K. Fatih (WALTER DE GRUYTER & CO, 2010)
In the present work, a method has been described for the determination of copper and lead by flame atomic absorption spectrometry (FAAS) after preconcentration and separation in water by ion exchange resin and coflotation. Purolite S-940, that is a strong cation exchanger, was used for preconcentration and separation of the trace metals as the first method. Optimum metal uptake conditions were investigated using batch systems These optimum conditions are: pH, contact time, the initial metal concentration and the amount of resin. Using results obtained from experiments of optimum conditions, Cu and Pb in water samples which were taken from ISKI (Water Authority for Istanbul) Kagithane and ISKI Buyukcekmece were enriched and determined by FAAS. The second method is a preconcentration and separation using hexamethylendithiocarbomate as a chelating agent for colloid flotation Cu and Pb from water The influences arising from pH, nitric acid concentration, amount of analytes, and sample volume on the recoveries were assessed Cu and Pb in water samples which were taken from ISKI Kagithane and ISKI Buyukcekmece were enriched and determined by FAAS. Results of these two methods are compared. Our results showed that two methods were very effective but flotation results higher than ion exchange.
Keywords: Ion-exchange; flotation; resin; preconcentration; separation; copper; lead; water; AAS; ATOMIC-ABSORPTION-SPECTROMETRY; EMISSION-SPECTROMETRY; SILICA-GEL; SAMPLES; HEXAMETHYLENEDITHIOCARBAMATE; PHOSPHATE; Chemistry